Age constraints on ductile deformation and long-term slip rates along the Karakoram fault zone, Ladakh - Phillips, R; Parrish, R; Searle, M (2004)
The dextral Karakoram fault zone, that bounds the southwestern margin of Tibet, is widely regarded as one of the major strike-slip faults that accommodates the eastward extrusion of the thickened crust of Tibet. In northern Ladakh, the Karakoram fault bounds the Pangong transpressional zone, with the active fault trace following the eastern margin of the range. Exhumation within this zone reveals mylonites that have absorbed much of the deformation along the fault. Two sets of dikes are evident within the main fault strand that bounds the transpressional zone. Whilst one dike set is concordant with the dominant foliation and shows mylonitic fabric, the youngest dike set are less deformed and cross-cut the shear zone fabric. Using U-Pb ID-TIMS data from five shear zone samples deformed by differing degrees, we infer that fault initiation occurred between 15.68±0.52 and 13.73±0.28 Ma. Since absolute offset is difficult to determine we couple these age constraints with suggested minimum and maximum offsets of the Baltoro-type granites. The offset range of 40-150 km reveals that the Karakoram fault has a long-term average slip-rate in the range 2.7-10.2 mm/year, the lower rate being compatible with GPS, InSAR and cosmogenic data for the fault. The small range of offset and low slip-rates do not support rapid, large-scale extrusion of Tibet along lithospheric-scale faults and strengthens the argument that Tibet does not behave in a rigid, plate-like, manner. © 2004 Elsevier B.V. All rights reserved.